Low-shrinkage recycled aggregate ultra-high performance concrete as well as preparation method and application thereof

Through pretreatment and optimization of particle size distribution, the ultra-high performance concrete formula of regenerated aggregates is solved, and the shrinkage and mechanical properties of ultra-high performance concrete of regenerated aggregates in the prior art is achieved, and low shrinkage, high strength and good construction are achieved The performance meets the development requirements of concrete technology and realizes the recycling of waste.

CN119241159AActive Publication Date: 2025-01-03QINGDAO UNIV OF TECH

Patent Information

Application Number
CN202411309186.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

After recycled aggregate ultra-high performance concrete replaces natural aggregate, it cannot achieve close accumulation of concrete raw materials, which has the disadvantage of large shrinkage, and the mechanical properties and working properties have significantly changed, which cannot meet the development requirements and application of concrete technology.

Method used

By pretreating the recycled aggregate, the particle size distribution and content are optimized, and combined with the theory of maximum bulk density, a low-shrinkage recycled aggregate ultra-high performance concrete formula is designed, using Polante cement, silica fume, natural river sand fine aggregate, recycled fine aggregate, The raw materials such as aggregates, natural basalt coarse aggregates, regenerated coarse aggregates, water reducing agents, carbon fibers and steel fibers are adopted to ensure that each component is closely packed and reduce the shrinkage of the concrete.

Benefits of technology

It achieves low shrinkage, high strength, high durability and good construction performance, reduces the risk of cracking caused by shrinkage of concrete materials, meets the requirements of mechanical properties and working performance, and saves energy and realizes the recycling of waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241159A_ABST
    Figure CN119241159A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ultra-high performance concrete, and particularly relates to low-shrinkage recycled aggregate ultra-high performance concrete as well as a preparation method and application thereof. The low-shrinkage recycled aggregate ultra-high performance concrete is prepared from the following raw materials in parts by weight: 840 to 860 parts of Portland cement, 140 to 160 parts of silica fume, 320 to 480 parts of natural river sand fine aggregate, 320 to 480 parts of recycled fine aggregate, 400 to 560 parts of natural basalt coarse aggregate, 240 to 400 parts of recycled coarse aggregate, 18 to 22 parts of water reducing agent, 40 to 60 parts of carbon fiber, 140 to 160 parts of steel fiber and 420 to 640 parts of water. The replacement rate of the regenerated fine aggregate for replacing the natural river sand fine aggregate is 40-60%, and the replacement rate of the regenerated coarse aggregate for replacing the natural basalt coarse aggregate is 30-50%. The prepared ultra-high performance concrete is good in fluidity, good in construction performance, low in shrinkage, high in strength and high in durability, the used recycled aggregate can save energy, cyclic utilization of waste is achieved, the method for treating the aggregate saves energy and reduces emission, and the ultra-high performance concrete is suitable for large-scale application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ultra-high performance concrete, and specifically relates to a low-shrinkage recycled aggregate ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] Concrete has become the most widely used civil engineering material due to its excellent performance. Ultra-high performance concrete uses fly ash, slag, limestone powder, kaolin and other industrial waste materials as admixtures, and is used with cement. It can improve performance while reducing the use of cement. Compared with ordinary concrete, it has the advantages of higher strength, high toughness, low porosity and environmental protection. However, with the continuous use of earth resources and the continuous development of the concrete industry, natural aggregates are constantly decreasing, and waste concrete materials are accumulating in large quantities. How to reduce the use of natural aggregates and how to reuse waste concrete have become hot topics of research today.

[0003] Recycled aggregate ultra-high performance concrete is a kind of ultra-high performance concrete made by replacing natural sand with recycled fine aggregate. The difference between recycled aggregate ultra-high performance concrete and ordinary ultra-high performance concrete lies in the difference in the use of aggregates. By using the waste concrete, processing it, obtaining recycled aggregate, and applying it to ultra-high performance concrete, the use of natural aggregate is reduced, which is in line with the sustainable development strategy of today's society.

[0004] The patent application publication number CN 115490448 A discloses a method for reducing the autogenous shrinkage of ultra-high performance concrete, high-strength concrete and high-strength mortar. Waste fired ceramics are crushed into waste ceramic regenerated sand, and the waste ceramic regenerated sand is used as all or part of the fine aggregate for preparing ultra-high performance concrete, high-strength concrete and high-strength mortar, but its 7d autogenous shrinkage is more than 50%. The patent application publication number CN 108285310 A discloses an ultra-high performance concrete prepared by using recycled fine aggregate from waste concrete and a preparation method thereof. The raw materials are: 570-630 parts of ordinary Portland cement, 270-320 parts of fly ash, 85-115 parts of silica fume, 25-35 parts of expansion agent, 300-800 parts of recycled fine aggregate, 300-800 parts of river sand, 180-220 parts of microfilament steel fiber, 18-22 parts of polycarboxylate water reducer, and 150-180 parts of water. Only recycled fine aggregate is used in different proportions to replace the more expensive natural fine aggregate. Although the compressive strength and flexural strength are improved, its shrinkage is not verified. The patent application publication number CN107235684A discloses a recycled fine aggregate ultra-high performance concrete and a method for using the same. The recycled fine aggregate belongs to Class I recycled fine aggregate, and its particle size range is 0.15-1.18 mm or 0.15-4.75 mm. The recycled fine aggregate replaces natural sand, and does not involve replacing natural coarse aggregate. At the same time, the preparation method is relatively complicated and requires autoclave curing. It can be seen that the above-mentioned recycled aggregate ultra-high performance concrete and its preparation method cannot achieve the compact stacking of concrete raw materials, and also have the disadvantage of large shrinkage. The working performance or mechanical properties of the ultra-high performance concrete after the recycled aggregate is replaced have changed significantly, and cannot meet the development requirements and applications of concrete technology. Summary of the invention

[0005] The purpose of the present invention is to provide a recycled aggregate ultra-high performance concrete and a preparation method and application thereof, so as to overcome the shortcomings of the prior art, pretreat the recycled aggregate, and partially replace the natural aggregate with the pretreated recycled aggregate. The prepared recycled aggregate ultra-high performance concrete not only has good fluidity, good construction performance, low shrinkage, high strength, and high durability, but also the recycled aggregate used can save energy and realize the recycling of waste materials. The method for treating aggregates saves energy and reduces emissions, and is suitable for large-scale promotion and application.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In one aspect, the present invention provides a low shrinkage recycled aggregate ultra-high performance concrete, which is composed of the following raw materials in parts by weight:

[0008] 840-860 parts of Portland cement, 140-160 parts of silica fume, 320-480 parts of natural river sand fine aggregate, 320-480 parts of recycled fine aggregate, 400-560 parts of natural basalt coarse aggregate, 240-400 parts of recycled coarse aggregate, 18-22 parts of water reducer, 40-60 parts of carbon fiber, 140-160 parts of steel fiber, and 420-640 parts of water.

[0009] The low-shrinkage recycled aggregate ultra-high performance concrete prepared by the present invention is easy to construct, has low shrinkage (reduced by about 10% compared with ordinary ultra-high performance concrete), and high strength (the compressive strength after 28 days can reach 146MPa, the splitting tensile strength can reach 17MPa, and the elastic modulus can reach 45MPa). In addition, the replacement rate of the recycled aggregate used to replace the natural fine aggregate is 40% to 60%, and at this replacement rate, the impact on UHPC is small, and the basic mechanical properties and working performance can be met.

[0010] Among the raw materials used in the present invention, the recycled aggregate used is obtained by crushing and screening concrete samples, and the aggregate in the concrete sample is a mixture of natural river sand fine aggregate and natural basalt. The present invention first calculates the particle size of natural fine aggregate river sand, natural basalt coarse aggregate, recycled fine aggregate, and recycled coarse aggregate through the most compact packing density theory, optimizes the content of each particle size segment of each natural aggregate (natural fine aggregate river sand, natural basalt coarse aggregate) and recycled aggregate (recycled fine aggregate, recycled coarse aggregate) in the low shrinkage recycled aggregate ultra-high performance concrete raw material, and then obtains various combinations of various particle sizes of natural fine aggregate river sand, natural basalt coarse aggregate, recycled fine aggregate and recycled coarse aggregate by screening, so that on the one hand, it plays a role of skeleton support, and on the other hand, it optimizes the particle grading so that each component is closely stacked, and the gap formed between the large particle size and the large particle size is filled by a smaller particle size, and the smaller particle size is filled by an aggregate of a smaller particle size, so that the porosity of the concrete is reduced, so that its strength meets the requirements. As for conventional ultra-high performance concrete, which does not contain coarse aggregate, the purpose of adding coarse aggregate is to reduce its shrinkage value, because the shrinkage of coarse aggregate itself is negligible.

[0011] The calculation formula for the relative content of each particle size segment of the aggregate used is as follows:

[0012]

[0013] Where: P Di The particle size is smaller than D i The volume fraction of particles is %; q is the particle size distribution modulus; D max and D min They are the maximum and minimum particle sizes of aggregate used in preparing low shrinkage recycled aggregate ultra-high performance concrete, μm.

[0014] The silica fume used as an admixture can reduce the amount of Portland cement used, thereby reducing CO2 emissions and saving energy.

[0015] The water reducer used is a polycarboxylic acid water reducer with a water reduction rate greater than 25%, which makes the cementitious material particles dispersed evenly, improves workability, increases fluidity, and reduces water consumption, thereby improving the mechanical properties and durability of the low-shrinkage recycled aggregate ultra-high performance concrete material.

[0016] The steel fibers used are steel fibers with a tensile strength greater than 25 GPa and a length of 8-12 mm; the carbon fibers are carbon fibers with a tensile strength greater than 30 GPa and a length of 0.18-0.22 mm.

[0017] Through the synergistic effect of the above-mentioned raw material components, the prepared low-shrinkage recycled aggregate ultra-high performance concrete not only has good fluidity, good construction performance, low shrinkage, high strength and high durability, but also the recycled aggregate used can save energy, realize the recycling of waste, and the method of processing aggregates saves energy and reduces emissions.

[0018] In a second aspect, the present invention provides a method for preparing the low shrinkage recycled aggregate ultra-high performance concrete according to the first aspect, comprising the following steps:

[0019] S1, adding a water reducing agent and carbon fiber into water and mixing evenly to obtain a first mixture;

[0020] S2, evenly mix Portland cement and silica fume and add them into the first mixture in S1 in batches, mix evenly, and obtain a second mixture;

[0021] S3, adding the steel fiber into the second mixture in S2, mixing evenly, to obtain a third mixture;

[0022] S4, mixing the natural river sand fine aggregate and the recycled fine aggregate evenly, and adding them to the third mixture in S3, mixing evenly, to obtain a fourth mixture;

[0023] S5, adding natural basalt coarse aggregate evenly to the fourth mixture in S4, mixing evenly, to obtain a fifth mixture;

[0024] S6. Add the recycled coarse aggregate evenly to the fifth mixture in S5, mix evenly, and obtain low shrinkage ultra-high performance concrete.

[0025] The raw material ratio and preparation method of the present invention follow the maximum packing density theory, and the particles of different particle sizes of the constituent materials are packed most closely in an optimal ratio, and are evenly mixed to obtain a low-shrinkage ultra-high performance concrete material. First, carbon fiber is added to water, which is beneficial for better dispersion in concrete and prevents agglomeration. Considering that the surface of recycled coarse aggregate is relatively fragile relative to natural aggregate, and the two aggregates collide and rub against each other to damage the recycled aggregate, the recycled coarse aggregate is added at the end, which can buffer the collision between the recycled coarse aggregate and the natural basalt aggregate, thereby reducing the influence on the mechanical properties and shrinkage properties of the prepared low-shrinkage ultra-high performance concrete material.

[0026] In order to further improve the replacement effect of recycled aggregate (recycled fine aggregate, recycled coarse aggregate) on natural aggregate (natural fine aggregate river sand, natural basalt coarse aggregate) and the coordination effect between the various components of the raw materials, the present application performs pretreatment on the recycled aggregate before remixing, namely, crushing, screening, wet treatment, acid treatment (recycled coarse aggregate) and carbonization treatment, so that the pretreated recycled aggregate can meet the requirements of the working performance, mechanical properties and shrinkage performance of concrete.

[0027] In a third aspect, the present invention provides a use of the low shrinkage recycled aggregate ultra-high performance concrete described in the first aspect in preparing ultra-high performance concrete with low shrinkage.

[0028] Beneficial effects of the present invention:

[0029] (1) The low shrinkage recycled aggregate ultra-high performance concrete material involved in the technical solution of the present invention has a fluidity of about 220 mm, indicating good fluidity and reducing the difficulty of construction of the ultra-high performance concrete material.

[0030] (2) The technical solution of the present invention involves a low-shrinkage recycled aggregate ultra-high performance concrete material, which has a 28-day compressive strength of up to 146MPa, a splitting tensile strength of up to 17MPa, and an elastic modulus of up to 45MPa. It has good mechanical properties and can greatly improve the safety performance of the material. The shrinkage performance is reduced by about 10% compared with ordinary ultra-high performance concrete, which can reduce the risk of cracking caused by shrinkage of concrete materials.

[0031] (3) The technical solution of the present invention relates to a recycled aggregate ultra-high performance concrete material, in which silica fume from industrial waste is used as the cementitious material, thereby reducing the amount of cement used and allowing industrial waste to be reused, thereby saving energy and protecting the environment.

[0032] (4) The technical solution of the present invention involves a recycled aggregate ultra-high performance concrete material, in which the recycled aggregate partially replaces the natural aggregate, thereby reusing the waste aggregate formed by the demolition of buildings without reducing its mechanical properties and working performance, reducing the use of natural aggregate, and is a reflection of the country's current sustainable development strategy.

[0033] (5) The technical solution of the present invention involves a method for processing recycled aggregates, which saves energy and reduces emissions. The method of processing recycled aggregates using CO2 saves energy and reduces emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart for preparing low shrinkage recycled aggregate ultra-high performance concrete according to Example 1 of the present invention. DETAILED DESCRIPTION

[0035] In order to solve the problem that the mechanical properties and working performance of the ultra-high performance concrete prepared by replacing natural aggregate with recycled aggregate are reduced, and it is impossible to obtain low-shrinkage recycled aggregate ultra-high performance concrete with good fluidity, good construction performance, low shrinkage, high strength, high durability and recycling of waste materials. The present invention provides a low-shrinkage recycled aggregate ultra-high performance concrete and a preparation method and application thereof.

[0036] A typical embodiment of the present invention provides a low shrinkage recycled aggregate ultra-high performance concrete, which is composed of the following raw materials in parts by weight:

[0037] 840-860 parts of Portland cement, 140-160 parts of silica fume, 320-480 parts of natural river sand fine aggregate, 320-480 parts of recycled fine aggregate, 400-560 parts of natural basalt coarse aggregate, 240-400 parts of recycled coarse aggregate, 18-22 parts of water reducer, 40-60 parts of carbon fiber, 140-160 parts of steel fiber, and 420-640 parts of water.

[0038] In some examples of this embodiment, the raw materials are composed of the following parts by weight: 850 parts of Portland cement, 150 parts of silica fume, 320-480 parts of natural river sand fine aggregate, 320-480 parts of recycled fine aggregate, 400-560 parts of natural basalt coarse aggregate, 240-400 parts of recycled coarse aggregate, 20 parts of water reducer, 50 parts of carbon fiber, 150 parts of steel fiber, and 440 parts of water;

[0039] Preferably, the Portland cement has a PO of not less than 42.5; and the SiO2 content in the silica fume is not less than 92wt.%.

[0040] The water reducing agent is a polycarboxylate water reducing agent having a water reducing rate greater than 25%;

[0041] The steel fiber has a tensile strength greater than 25 GPa and a length of 8 to 12 mm;

[0042] The carbon fiber has a tensile strength greater than 30 GPa and a length of 0.18 to 0.22 mm.

[0043] In some examples of this embodiment, the particle size of the natural river sand fine aggregate and the particle size of the recycled fine aggregate are both 0.155 to 2.36 mm;

[0044] The particle size of the natural basalt coarse aggregate and the particle size of the recycled coarse aggregate are both 2.36-8.36 mm. In some examples of this embodiment, the composition of the natural river sand fine aggregate is as follows:

[0045] 80-120 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0046] 112-168 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0047] 128-192 parts of natural river sand fine aggregate with a particle size of 1.25-2.36 mm;

[0048] Preferably, the composition of the recycled fine aggregate is as follows:

[0049] 80-120 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0050] 112-168 parts of recycled fine aggregate with a particle size of 0.315-1.25 mm;

[0051] 128-192 parts of recycled fine aggregate with a particle size of 1.25-2.36 mm;

[0052] Preferably, the composition of the natural basalt coarse aggregate is as follows:

[0053] 100-140 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0054] 140-196 parts of natural basalt coarse aggregate with a particle size of 4.75-6.12 mm;

[0055] 160-224 parts of natural basalt coarse aggregate with a particle size of 6.12-8.36 mm;

[0056] Preferably, the composition of the recycled coarse aggregate is as follows:

[0057] 60-100 parts of recycled coarse aggregate with a particle size of 2.36-4.75 mm;

[0058] 84-140 parts of recycled coarse aggregate with a particle size of 4.75-6.12 mm;

[0059] 96-160 parts of recycled coarse aggregate with a particle size of 6.12-8.36 mm.

[0060] In some examples of this embodiment, the composition of the natural river sand fine aggregate is as follows:

[0061] 120 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0062] 168 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0063] 192 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0064] Preferably, the composition of the recycled fine aggregate is as follows:

[0065] 80 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0066] 112 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0067] 128 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0068] Preferably, the composition of the natural basalt coarse aggregate is as follows:

[0069] 140 parts of natural basalt coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0070] 196 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0071] 224 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0072] Preferably, the composition of the recycled coarse aggregate is as follows:

[0073] 60 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0074] 84 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0075] 96 parts of recycled coarse aggregate with particle size of 6.12 to 8.36 mm.

[0076] In some examples of this embodiment, the composition of the natural river sand fine aggregate is as follows:

[0077] 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0078] 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0079] 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0080] Preferably, the composition of the recycled fine aggregate is as follows:

[0081] 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0082] 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0083] 160 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0084] Preferably, the composition of the natural basalt coarse aggregate is as follows:

[0085] 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0086] 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0087] 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0088] Preferably, the composition of the recycled coarse aggregate is as follows:

[0089] 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0090] 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0091] 128 parts of recycled coarse aggregate with particle size of 6.12 to 8.36 mm.

[0092] In some examples of this embodiment, the composition of the natural river sand fine aggregate is as follows:

[0093] 80 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0094] 112 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0095] 128 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0096] Preferably, the composition of the recycled fine aggregate is as follows:

[0097] 120 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0098] 168 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0099] 192 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0100] Preferably, the composition of the natural basalt coarse aggregate is as follows:

[0101] 100 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0102] 140 parts of natural basalt coarse aggregate with a particle size of 4.75-6.12 mm;

[0103] 160 parts of natural basalt coarse aggregate with a particle size of 6.12-8.36 mm;

[0104] Preferably, the composition of the recycled coarse aggregate is as follows:

[0105] 100 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0106] 140 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0107] 160 parts of recycled coarse aggregate with particle size of 6.12-8.36 mm.

[0108] Another typical embodiment of the present invention provides a method for preparing the low shrinkage recycled aggregate ultra-high performance concrete in the first typical embodiment, comprising the following steps:

[0109] S1, adding a water reducing agent and carbon fiber into water and mixing evenly to obtain a first mixture;

[0110] S2, evenly mix Portland cement and silica fume and add them into the first mixture in S1 in batches, mix evenly, and obtain a second mixture;

[0111] S3, adding the steel fiber into the second mixture in S2, mixing evenly, to obtain a third mixture;

[0112] S4, mixing the natural river sand fine aggregate and the recycled fine aggregate evenly, and adding them to the third mixture in S3, mixing evenly, to obtain a fourth mixture;

[0113] S5, adding natural basalt coarse aggregate evenly to the fourth mixture in S4, mixing evenly, to obtain a fifth mixture;

[0114] S6. Add the recycled coarse aggregate evenly to the fifth mixture in S5, mix evenly, and obtain low shrinkage ultra-high performance concrete.

[0115] In some examples of this embodiment, in S4, the recycled fine aggregate is pre-treated, and the specific processing steps are as follows:

[0116] (1) crushing and screening concrete to obtain crushed recycled fine aggregate;

[0117] (2) mixing the recycled fine aggregate in step (1) with water for humidification treatment, and controlling the moisture content of the recycled fine aggregate;

[0118] (3) carbonizing the recycled fine aggregate after the humidification treatment in step (2) to obtain recycled fine aggregate with a particle size of 0.155 to 2.36 mm;

[0119] Or, in S5, the recycled coarse aggregate is pretreated, and the specific processing steps are as follows:

[0120] (1) crushing and screening concrete to obtain crushed recycled coarse aggregate;

[0121] (2) mixing the recycled coarse aggregate in step (1) with water for humidification treatment, and controlling the moisture content of the recycled coarse aggregate;

[0122] (3) treating the recycled coarse aggregate after the humidification treatment in step (2) with acid, washing, and drying to obtain acid-treated recycled coarse aggregate;

[0123] (4) carbonizing the recycled coarse aggregate after the acid treatment in step (3) to obtain recycled coarse aggregate with a particle size of 2.36 to 8.36 mm;

[0124] Preferably, during the pretreatment of the recycled fine aggregate or recycled coarse aggregate, the carbonization treatment conditions are: 20-30°C, relative humidity 50-70%, and air pressure 0.5-1 mPa for 20-24 hours;

[0125] Preferably, during the pretreatment of the recycled fine aggregate or recycled coarse aggregate, after the humidification treatment, the moisture content of the recycled fine aggregate is 9-12wt.%, and the moisture content of the recycled coarse aggregate is 2-5wt.%;

[0126] Preferably, during the pretreatment of the recycled coarse aggregate, the acid treatment is performed by using 0.12-2 mol / L dilute hydrochloric acid for immersion for 20-24 hours.

[0127] Another typical embodiment of the present invention provides the use of the low shrinkage recycled aggregate ultra-high performance concrete in the first typical embodiment in the preparation of ultra-high performance concrete with low shrinkage.

[0128] The present invention is further described in detail below in conjunction with specific embodiments:

[0129] In the following examples, polycarboxylate water reducer was purchased from Shandong Boke Chemical Co., Ltd., and retarder was purchased from Shanxi Zhengda Longqi Trading Co., Ltd.

[0130] Example 1

[0131] A low shrinkage recycled aggregate ultra-high performance concrete material, comprising the following raw materials in parts by weight: (recycled coarse aggregate replaces 30%, recycled fine aggregate replaces 40%)

[0132] 120 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0133] 168 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0134] 192 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0135] 80 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0136] 112 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0137] 128 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0138] 140 parts of natural basalt coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0139] 196 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0140] 224 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0141] 60 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0142] 84 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0143] 96 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0144] 150 parts of silica fume;

[0145] Water-cement ratio 0.185;

[0146] 20 parts of polycarboxylate water reducer;

[0147] 150 parts of 8-12mm steel fiber;

[0148] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0149] PO 42.5 cement 850 parts.

[0150] The method for preparing the above-mentioned low shrinkage recycled aggregate ultra-high performance concrete material is prepared according to the following steps:

[0151] S1. Mix the polycarboxylate water reducer, carbon fiber and water in a mixer for 1 min to make the water reducer and carbon fiber more evenly dispersed;

[0152] S2, evenly mix Portland cement and silica fume and add them into the S1 mixture in batches, mix and stir for 2 minutes;

[0153] S3, adding steel fiber into S2 mixture, mixing and stirring for 2 minutes;

[0154] S4, mix the natural river sand fine aggregate and the laboratory concrete sample recycled fine aggregate evenly, add them into the S3 mixture, and mix and stir for 1 minute;

[0155] S5. Add natural basalt coarse aggregate evenly into the S4 mixture and mix for 1 minute.

[0156] S6. Add the recycled coarse aggregate of the laboratory concrete sample evenly into the S5 mixture, mix and stir for 3 minutes to obtain a low shrinkage ultra-high performance concrete material.

[0157] Among them, in S4, the recycled fine aggregate is pretreated, and the specific processing steps are as follows:

[0158] (1) The concrete sample is crushed and mechanically ground to make the recycled fine aggregates collide and rub against each other to remove the surface mortar, thereby improving the particle shape of the recycled fine aggregates;

[0159] (2) Mixing the recycled fine aggregate in step (1) with water for humidification treatment, and controlling the moisture content of the recycled fine aggregate; since the recycled aggregate has a high water absorption capacity, the humidification treatment is beneficial to ensuring its working performance, and can also be used for later internal curing of concrete, which can reduce the shrinkage of concrete. The moisture content of the recycled fine aggregate is controlled between 9% and 12%. The recycled aggregate within this moisture content control range can meet both the working performance and the mechanical and shrinkage performance requirements.

[0160] (3) The recycled fine aggregate subjected to the humidification treatment in step (2) is subjected to carbonization treatment, and the substances generated by the reaction are gradually precipitated on the surface of the recycled fine aggregate, thereby reinforcing and repairing the recycled fine aggregate to a recycled fine aggregate with a particle size of 0.155 to 2.36 mm.

[0161] Among them, in S5, the recycled coarse aggregate is pretreated, and the specific processing steps are as follows:

[0162] (1) The laboratory concrete samples were crushed and mechanically ground to make the recycled coarse aggregates collide and rub against each other to remove the surface mortar, thereby improving the particle shape of the recycled coarse aggregates;

[0163] (2) The recycled coarse aggregate in step (1) is mixed with water for humidification treatment, and the moisture content of the recycled coarse aggregate is controlled; since the recycled aggregate has a high water absorption capacity, the humidification treatment is beneficial to ensuring its working performance, and can also be used for later internal curing of concrete, which can reduce the shrinkage of concrete. The moisture content of the recycled coarse aggregate is controlled between 2-5wt.%, and the recycled aggregate within this moisture content control range can meet both the working performance and the mechanical and shrinkage performance requirements.

[0164] (3) soaking the recycled coarse aggregate subjected to the humidification treatment in step (2) in a dilute hydrochloric acid solution with a concentration of 0.12 mol / L for 24 h, rinsing with distilled water after soaking to remove residual hydrochloric acid on the surface, and then drying to remove the old mortar layer on the surface of the particles;

[0165] (4) The recycled coarse aggregate treated with acid in step (3) is carbonized at 20° C., relative humidity 50%, and air pressure 0.5 MPa for 24 h. The substances generated by the reaction will gradually precipitate on the surface of the recycled coarse aggregate, thereby reinforcing and repairing the recycled coarse aggregate to obtain recycled coarse aggregate with a particle size of 2.36 to 8.36 mm.

[0166] Example 2

[0167] The difference from Example 1 is that the ratio of recycled aggregate replacing natural aggregate is different; other raw material proportions and preparation methods are exactly the same as those in Example 1.

[0168] The low shrinkage recycled aggregate ultra-high performance concrete material includes the following raw materials by weight: (recycled coarse aggregate replaces 40%, recycled fine aggregate replaces 50%)

[0169] 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0170] 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0171] 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0172] 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0173] 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0174] 160 parts of laboratory recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0175] 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0176] 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0177] 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0178] 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0179] 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0180] 128 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0181] 150 parts of silica fume;

[0182] Water-cement ratio 0.185;

[0183] 20 parts of polycarboxylate water reducer;

[0184] 150 parts of 8-12mm steel fiber;

[0185] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0186] PO 42.5 cement 850 parts.

[0187] Example 3

[0188] The difference from Example 1 is that the ratio of recycled aggregate replacing natural aggregate is different; other raw material proportions and preparation methods are exactly the same as those in Example 1.

[0189] Low shrinkage recycled aggregate ultra-high performance concrete material, comprising the following raw materials in parts by weight: (50% of recycled coarse aggregate is replaced by 50% of recycled fine aggregate, and 60% of recycled fine aggregate is replaced by 60%)

[0190] 80 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0191] 112 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0192] 128 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0193] 120 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0194] 168 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0195] 192 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0196] 100 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0197] 140 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0198] 160 parts of natural basalt coarse aggregate with a particle size of 6.12-8.36 mm;

[0199] 100 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0200] 140 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0201] 160 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0202] 150 parts of silica fume;

[0203] Water-cement ratio 0.185;

[0204] 20 parts of polycarboxylate water reducer;

[0205] 150 parts of 8-12mm steel fiber;

[0206] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0207] PO 42.5 cement 850 parts.

[0208] Comparative Example 1

[0209] Low shrinkage recycled aggregate ultra-high performance concrete material, including the following raw materials in parts by weight:

[0210] 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0211] 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0212] 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0213] 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0214] 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0215] 160 parts of laboratory recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0216] 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0217] 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0218] 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0219] 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0220] 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0221] 128 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0222] 150 parts of silica fume;

[0223] Water-cement ratio 0.185;

[0224] 20 parts of polycarboxylate water reducer;

[0225] 150 parts of 8-12mm steel fiber;

[0226] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0227] PO 42.5 cement 850 parts.

[0228] Different from Example 2, the preparation method is as follows: the recycled fine aggregate and the recycled coarse aggregate are not pretreated, and all the raw materials of Example 2 are directly mixed at one time.

[0229] Comparative Example 2

[0230] Low shrinkage recycled aggregate ultra-high performance concrete material, including the following raw materials in parts by weight:

[0231] 400 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0232] 400 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0233] 480 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0234] 320 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0235] 150 parts of silica fume;

[0236] Water-cement ratio 0.185;

[0237] 20 parts of polycarboxylate water reducer;

[0238] 150 parts of 8-12mm steel fiber;

[0239] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0240] PO 42.5 cement 850 parts.

[0241] The difference from Example 2 is that among the raw materials of the low shrinkage recycled aggregate ultra-high performance concrete material, all natural river sand fine aggregates are natural river sand fine aggregates with a particle size of 0.315-1.25 mm, all recycled fine aggregates are recycled fine aggregates with a particle size of 0.315-1.25 mm, all natural basalt coarse aggregates are natural basalt coarse aggregates with a particle size of 4.75-6.12 mm, and all recycled coarse aggregates are recycled coarse aggregates with a particle size of 4.75-6.12 mm. The other components and contents remain unchanged; the preparation method is the same as that of Example 2.

[0242] Comparative Example 3

[0243] Low shrinkage recycled aggregate ultra-high performance concrete material, including the following raw materials in parts by weight:

[0244] 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0245] 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0246] 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0247] 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0248] 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0249] 160 parts of laboratory recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0250] 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0251] 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0252] 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0253] 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0254] 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0255] 128 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0256] 150 parts of silica fume;

[0257] Water-cement ratio 0.185;

[0258] 20 parts of polycarboxylate water reducer;

[0259] 150 parts of 8-12mm steel fiber;

[0260] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0261] PO 42.5 cement 850 parts.

[0262] The raw material composition is the same as that in Example 2. The difference from Example 2 is that in the preparation method, during the pretreatment of the recycled fine aggregate and the recycled fine aggregate, after pre-wetting treatment, the moisture content of the recycled coarse aggregate is 6wt.%, and the moisture content of the recycled fine aggregate is 8wt.%.

[0263] Comparative Example 4

[0264] Low shrinkage recycled aggregate ultra-high performance concrete material, including the following raw materials in parts by weight:

[0265] 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm;

[0266] 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm;

[0267] 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm;

[0268] 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm;

[0269] 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm;

[0270] 160 parts of laboratory recycled fine aggregate with a particle size of 1.25 to 2.36 mm;

[0271] 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm;

[0272] 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0273] 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0274] 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm;

[0275] 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm;

[0276] 128 parts of recycled coarse aggregate with a particle size of 6.12 to 8.36 mm;

[0277] 150 parts of silica fume;

[0278] Water-cement ratio 0.185;

[0279] 20 parts of polycarboxylate water reducer;

[0280] 150 parts of 8-12mm steel fiber;

[0281] 50 parts of 0.18-0.22 mm carbon nanofibers;

[0282] PO 42.5 cement 850 parts.

[0283] The raw material composition is the same as that in Example 2. The difference from Example 2 is that in the preparation method, during the pretreatment of the recycled fine aggregate and the recycled fine aggregate, after humidification treatment, the moisture content of the recycled coarse aggregate is 1wt.%, and the moisture content of the recycled fine aggregate is 15wt.%.

[0284] Performance Testing

[0285] The standard specimens of the low shrinkage recycled aggregate ultra-high performance concrete materials described in Examples 1 to 3 and Comparative Examples 1 to 4 were prepared and subjected to compressive strength, splitting tensile strength, elastic modulus and shrinkage tests after standard curing for 28 days. The experimental data are shown in Table 1.

[0286] Table 1 Test data of low shrinkage recycled aggregate ultra-high performance concrete materials

[0287]

[0288] From Table 1, it can be seen that the compressive strength of all embodiments of the present invention is greater than 120MPa, the splitting tensile strength is greater than 10MPa, and the elastic modulus is greater than 34GPa, indicating that the mechanical properties are good. For ultra-high performance concrete, its apparent density is generally not less than 2500kg·m 3 Generally speaking, the greater the apparent density, the denser the concrete, the smaller the porosity, and the higher the compressive strength. According to the data of Examples 1 to 3, compared with Examples 2 and 3, the recycled aggregate with a low substitution rate in Example 1 has relatively better mechanical properties and shrinkage values. The ratio of the selected materials in Example 2 of the present invention is optimal and more economical than that in Example 1.

[0289] The reason why the performance of Comparative Example 1 is reduced relative to Example 2 is that if the recycled aggregate is not pretreated, part of the old mortar will adhere to the surface of the recycled aggregate. Therefore, during the mixed preparation, the bonding strength between the old mortar layer on the surface and the new mortar will decrease, resulting in a decrease in performance; the main reason why the performance of Comparative Example 2 is reduced relative to Example 2 is that if the particle size is not graded, the aggregates that fill the gaps between the aggregates will decrease, resulting in a greater porosity of the concrete, resulting in a decrease in performance. The performance of Comparative Examples 3 and 4 is also reduced relative to Example 2. The reason why the performance decrease is relatively small is that the moisture content is not much different from that of the embodiment, that is, the actual water-cement ratio in the comparative example is not much different from the actual water-cement ratio in the embodiment.

[0290] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low shrinkage recycled aggregate ultra-high performance concrete, characterized in that: It is composed of the following raw materials in parts by weight: 840-860 parts of Portland cement, 140-160 parts of silica fume, 320-480 parts of natural river sand fine aggregate, 320-480 parts of recycled fine aggregate, 400-560 parts of natural basalt coarse aggregate, 240-400 parts of recycled coarse aggregate, 18-22 parts of water reducer, 40-60 parts of carbon fiber, 140-160 parts of steel fiber, and 420-640 parts of water.

2. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: 850 parts of Portland cement, 150 parts of silica fume, 320-480 parts of natural river sand fine aggregate, 320-480 parts of recycled fine aggregate, 400-560 parts of natural basalt coarse aggregate, 240-400 parts of recycled coarse aggregate, 20 parts of water reducer, 50 parts of carbon fiber, 150 parts of steel fiber, and 440 parts of water; Preferably, the Portland cement is a Portland cement with a PO of not less than 42.5; the SiO2 content in the silica fume is not less than 92wt.%; The water reducing agent is a polycarboxylate water reducing agent having a water reducing rate greater than 25%; The steel fiber has a tensile strength greater than 25 GPa and a length of 8 to 12 mm; The carbon fiber has a tensile strength greater than 30 GPa and a length of 0.18 to 0.22 mm.

3. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 1 or 2, characterized in that: The particle size of the natural river sand fine aggregate and the particle size of the recycled fine aggregate are both 0.155-2.36 mm; The particle size of the natural basalt coarse aggregate and the particle size of the recycled coarse aggregate are both 2.36-8.36 mm.

4. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 3, characterized in that: The composition of the natural river sand fine aggregate is as follows: 80-120 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm; 112-168 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm; 128-192 parts of natural river sand fine aggregate with a particle size of 1.25-2.36 mm; Preferably, the composition of the recycled fine aggregate is as follows: 80-120 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm; 112-168 parts of recycled fine aggregate with a particle size of 0.315-1.25 mm; 128-192 parts of recycled fine aggregate with a particle size of 1.25-2.36 mm; Preferably, the composition of the natural basalt coarse aggregate is as follows: 100-140 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm; 140-196 parts of natural basalt coarse aggregate with a particle size of 4.75-6.12 mm; 160-224 parts of natural basalt coarse aggregate with a particle size of 6.12-8.36 mm; Preferably, the composition of the recycled coarse aggregate is as follows: 60-100 parts of recycled coarse aggregate with a particle size of 2.36-4.75 mm; 84-140 parts of recycled coarse aggregate with a particle size of 4.75-6.12 mm; 96-160 parts of recycled coarse aggregate with a particle size of 6.12-8.36 mm.

5. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 4, characterized in that: The composition of the natural river sand fine aggregate is as follows: 120 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm; 168 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm; 192 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the recycled fine aggregate is as follows: 80 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm; 112 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm; 128 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the natural basalt coarse aggregate is as follows: 140 parts of natural basalt coarse aggregate with a particle size of 2.36 to 4.75 mm; 196 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm; 224 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm; Preferably, the composition of the recycled coarse aggregate is as follows: 60 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm; 84 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm; 96 parts of recycled coarse aggregate with particle size of 6.12 to 8.36 mm.

6. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 4, characterized in that: The composition of the natural river sand fine aggregate is as follows: 100 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm; 140 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm; 160 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the recycled fine aggregate is as follows: 100 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm; 140 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm; 160 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the natural basalt coarse aggregate is as follows: 120 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm; 168 parts of natural basalt coarse aggregate with a particle size of 4.75 to 6.12 mm; 192 parts of natural basalt coarse aggregate with a particle size of 6.12 to 8.36 mm; Preferably, the composition of the recycled coarse aggregate is as follows: 80 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm; 112 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm; 128 parts of recycled coarse aggregate with particle size of 6.12 to 8.36 mm.

7. The low shrinkage recycled aggregate ultra-high performance concrete according to claim 4, characterized in that: The composition of the natural river sand fine aggregate is as follows: 80 parts of natural river sand fine aggregate with a particle size of 0.155-0.315 mm; 112 parts of natural river sand fine aggregate with a particle size of 0.315-1.25 mm; 128 parts of natural river sand fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the recycled fine aggregate is as follows: 120 parts of recycled fine aggregate with a particle size of 0.155-0.315 mm; 168 parts of recycled fine aggregate with a particle size of 0.315 to 1.25 mm; 192 parts of recycled fine aggregate with a particle size of 1.25 to 2.36 mm; Preferably, the composition of the natural basalt coarse aggregate is as follows: 100 parts of natural basalt coarse aggregate with a particle size of 2.36-4.75 mm; 140 parts of natural basalt coarse aggregate with a particle size of 4.75-6.12 mm; 160 parts of natural basalt coarse aggregate with a particle size of 6.12-8.36 mm; Preferably, the composition of the recycled coarse aggregate is as follows: 100 parts of recycled coarse aggregate with a particle size of 2.36 to 4.75 mm; 140 parts of recycled coarse aggregate with a particle size of 4.75 to 6.12 mm; 160 parts of recycled coarse aggregate with particle size of 6.12-8.36 mm.

8. A method for preparing the low shrinkage recycled aggregate ultra-high performance concrete according to any one of claims 1 to 7, characterized in that: The steps include: S1, adding a water reducing agent and carbon fiber into water and mixing evenly to obtain a first mixture; S2, evenly mix Portland cement and silica fume and add them into the first mixture in S1 in batches, mix evenly, and obtain a second mixture; S3, adding the steel fiber into the second mixture in S2, mixing evenly, to obtain a third mixture; S4, mixing the natural river sand fine aggregate and the recycled fine aggregate evenly, and adding them to the third mixture in S3, mixing evenly, to obtain a fourth mixture; S5, adding natural basalt coarse aggregate evenly to the fourth mixture in S4, mixing evenly, to obtain a fifth mixture; S6. Add the recycled coarse aggregate evenly to the fifth mixture in S5, mix evenly, and obtain low shrinkage ultra-high performance concrete.

9. The method for preparing low shrinkage recycled aggregate ultra-high performance concrete according to claim 8, characterized in that: In S4, the recycled fine aggregate is pretreated, and the specific processing steps are as follows: (1) crushing and screening concrete to obtain crushed recycled fine aggregate; (2) mixing the recycled fine aggregate in step (1) with water for humidification treatment, and controlling the moisture content of the recycled fine aggregate; (3) carbonizing the recycled fine aggregate after the humidification treatment in step (2) to obtain recycled fine aggregate with a particle size of 0.155 to 2.36 mm; Or, in S5, the recycled coarse aggregate is pretreated, and the specific processing steps are as follows: (1) crushing and screening concrete to obtain crushed recycled coarse aggregate; (2) mixing the recycled coarse aggregate in step (1) with water for humidification treatment, and controlling the moisture content of the recycled coarse aggregate; (3) treating the recycled coarse aggregate after the humidification treatment in step (2) with acid, washing, and drying to obtain acid-treated recycled coarse aggregate; (4) carbonizing the recycled coarse aggregate after the acid treatment in step (3) to obtain recycled coarse aggregate with a particle size of 2.36 to 8.36 mm; Preferably, during the pretreatment of the recycled fine aggregate or recycled coarse aggregate, the carbonization treatment conditions are: 20-30°C, relative humidity 50-70%, and air pressure 0.5-1 mPa for 20-24 hours; Preferably, during the pretreatment of the recycled fine aggregate or recycled coarse aggregate, after the humidification treatment, the moisture content of the recycled fine aggregate is 9-12wt.%, and the moisture content of the recycled coarse aggregate is 2-5wt.%; Preferably, during the pretreatment of the recycled coarse aggregate, the acid treatment is performed by using 0.12-2 mol / L dilute hydrochloric acid for immersion for 20-24 hours.

10. Use of the low shrinkage recycled aggregate ultra-high performance concrete according to any one of claims 1 to 5 in preparing ultra-high performance concrete with low shrinkage.

Citation Information

Patent Citations

  • Ultra-high-performance concrete including regenerated fine aggregates and application method thereof

    CN107235684A

  • Ultra-high performance concrete prepared from waste concrete recycled fine aggregate and preparation method thereof

    CN108285310A

  • Method for reducing self-constriction of ultra-high performance concrete, high-strength concrete and high-strength mortar

    CN115490448A

  • Designing of mix ratio of high-performance recycled concrete

    CN106904894A

  • Recycled concrete doped with short-cut basalt fibers and recycled coarse aggregate

    CN107010896A

Cited By

  • Recycled aggregate close packing method established based on volume expansion and contraction putting principle

    CN120850435A

  • A close-packing method of recycled aggregate based on volume expansion and contraction principle

    CN120850435B